2014
DOI: 10.1128/aac.02762-14
|View full text |Cite
|
Sign up to set email alerts
|

Double Mutation in the pfmdr1 Gene Is Associated with Emergence of Chloroquine-Resistant Plasmodium falciparum Malaria in Eastern India

Abstract: Malaria is a major public health problem in tropical and subtropical countries, including India. This study elucidates the cause of chloroquine treatment failure (for Plasmodium falciparum infection) before the introduction of artemisinin combination therapy. One hundred twenty-six patients were randomized to chloroquine treatment, and the therapeutic efficacy was monitored from days 1 to 28. An in vitro susceptibility test was performed with all isolates. Parasitic DNA was isolated, followed by PCR and restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The high rates of CQ treatment failure indicated the enormous CQ pressure over this parasite population, as more than 40% of cases were produced in vivo CQ resistance (Das et al., 2014). The second major finding of this study have provided the evidence of increased in vitro chloroquine resistance as well as rapid rise in candidate gene mutations ( pfcrt and pfmdr1 ) in subsequent years, after withdrawal of chloroquine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rates of CQ treatment failure indicated the enormous CQ pressure over this parasite population, as more than 40% of cases were produced in vivo CQ resistance (Das et al., 2014). The second major finding of this study have provided the evidence of increased in vitro chloroquine resistance as well as rapid rise in candidate gene mutations ( pfcrt and pfmdr1 ) in subsequent years, after withdrawal of chloroquine.…”
Section: Discussionmentioning
confidence: 99%
“…increase in IC 50 of CQ (Fidock et al., 2000, Duraisingh and Cowman, 2005). Our study confirmed that, CQ resistance was highly associated with CVMN T - Y YSND and CVMN T - Y YSN Y haplotype in Kolkata, which was identical with the previous finding reported from different parts of India (Vinayak et al., 2003, Sharma, 2005, Das et al., 2014). In Purulia, CQ treatment failure (60.71% ETF and, 33.33% LTF, in 2008; 60.47% ETF and 37.5% LTF in 2009) was found to associated with CVMNK- Y YSN Y allele, which was quite uncommon in India.…”
Section: Discussionmentioning
confidence: 99%
“…After adequate PCR amplification of different amplicon, sequencing reactions were carried out in 3730xl genetic analyzer (Applied Biosystems) ≥2× coverage using an ABI Prism Big Dye Terminator cycle sequencing ready reaction kit. In the sequencing PCR reaction the final master mix volume was 20 µl, consisting of 1 µl of Terminator ready reaction mix (TRR), 3.2 pmol of gene-specific primer, and 0.5× sequencing buffer [ 28 ]. Sequencing experiments were carried out at the Indian Institute of Technology, Kharagpur (IIT, Kharagpur), and Sci Genome Company (Kochin).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing experiments were carried out at the Indian Institute of Technology, Kharagpur (IIT, Kharagpur), and Sci Genome Company (Kochin). Electrophoregrams were visualized and analysed with CEQ 2000 genetic analysis system software (Beckman Coulter), and the sequencing traits were translated in the translation tool, available online at the Expert Protein Analysis System proteomic server [ 28 ]. Translated sequences were aligned online by the multiple sequence alignment tool ClustalW2 [ 28 ] and compared with the wild-type allele sequences (GenBank accession numbers, X98123 for pvdhfr , AY186730 for pvdhps ).…”
Section: Methodsmentioning
confidence: 99%
“…Some reports have associated a rise in the prevalence of pfmdr1 86Y alleles with increasing CQ resistance [11][12]25]. The low prevalence of pfmdr1 86Y in Adamawa and Yobe raises the possibility that CQ may be effective against P. falciparum malaria in North-Eastern Nigeria once again, although this would be presumably tempered by CQ-resistance associated mutations in pfcrt, which we have not assayed here.…”
Section: Discussionmentioning
confidence: 79%